The Effect of Infrastructure, Labor Force, and Market Size on Domestic Investment in Indonesia - Rafiqah Nur Izzati; Lucky Rachmawati (Journal of Current Studies in SDGs, 2025)
Objective: As one of the components of economic growth in Indonesia, domestic investment experiences inequality problems. This study aims to identify the influence of infrastructure, workforce, and market size on domestic investment in Indonesia in 2023. Method: This study uses a quantitative approach using multiple linear regression analysis methods on cross-section data from 34 provinces in Indonesia. The data used in this study comes from the Indonesian Central Bureau of Statistics. Results: After a quantitative approach using multiple linear regression analysis methods, the results obtained are: (1) infrastructure in the form of road stability has a significant positive effect on domestic investment or Domestic Investment (PMDN); (2) market size in the form of Gross Regional Domestic Product (PDRB) has a significant positive effect on domestic investment; (3) the workforce represented by the number of workers has a negative effect on domestic investment, but is not significant; and (4) together, there is an influence of infrastructure, workforce, and market size on the value of domestic investment. Novelty: In contrast to most previous studies that focused more on analyzing foreign investment, this study focuses on the determinants of domestic investment (PMDN) in Indonesia.